Performance Study of Enhanced Non-Linear PID Control Applied on Brushless DC Motor - Mohamed Shamseldin; Mohamed Abdel Ghany; Abdel Ghany Mohamed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper presents an enhanced nonlinear PID (NPID) controller to follow a preselected speed profile of brushless DC motor drive system. This objective should be achieved regardless the parameter variations, and external disturbances. The performance of enhanced NPID controller will be investigated by comparing it with linear PID control and fractional order PID (FOPID) control. These controllers are tested for both speed regulation and speed tracking. The optimal parameters values of each control technique were obtained using Genetic Algorithm (GA) based on a certain cost function. Results shows that the proposed NPID controller has better performance among other techniques (PID and FOPID controller).